Sustainable Supply Chain and Design Optimization: A Bibliometric Review - Bista, Aashish; Kaphle, Bhawana; Adhikari, Bina; Rumba, Jamuna (International Journal of Atharva, 2026)
Background: Global supply chains face unprecedented disruptions, environmental pressures, and evolving market demands, necessitating a critical transformation toward sustainability and resilience. Academic research on Sustainable Supply Chain Management (SSCM) has consequently grown exponentially, creating a vast and multidisciplinary body of literature that requires consolidation to identify core intellectual trends and future directions. Objective: This study aimed to conduct an extensive bibliometric analysis to map the intellectual structure and thematic evolution of SSCM research from 2021 to 2025, with a specific focus on the intersections of green logistics, design optimization, the circular economy, and supply chain resilience. Methods: A quantitative bibliometric methodology was employed. Data was collected from the Dimensions.ai database for Open Access journal articles published between 2021 and 2025, using a targeted search query. The analysis involved performance indicators (e.g., publication growth, influential journals) and science mapping. Network visualizations of keyword co-occurrence and bibliographic coupling were created using VOSviewer, complemented by textual analysis of titles via WordSift.org. Findings: The analysis reveals a near-exponential growth in publications, from 28 in 2021 to 158 in 2025. The field exhibits a dual publication ecosystem, with high-volume outlets like Sustainability facilitating broad dissemination and high-impact journals like the Journal of Cleaner Production setting academic benchmarks. Thematic clusters center on technology-enabled resilience (e.g., AI, blockchain, digital twins) and circular economy integration. A striking finding is the definitive pivot toward digitalization (AI, IoT, blockchain) as the central enabler for achieving sustainability and resilience goals. Furthermore, the research community shows strong cohesion, as indicated by very high bibliographic coupling strength, suggesting a mature but potentially insular knowledge base. Conclusion: The SSCM field has rapidly evolved from a conceptual foundation into a complex, technology-driven research arena focused on systemic resilience and circularity. The convergence of digital intelligence with sustainability imperatives is forging a new paradigm for adaptive and transparent supply networks. Future research must address the gap between high-impact theory and practical implementation, consciously foster interdisciplinary innovation to avoid intellectual insularity, and develop strategies scalable for small and medium-sized enterprises and emerging economies. Novelty: This study provides a unique and focused temporal analysis (2021-2025) that captures the accelerated evolution of the SSCM field in the post-pandemic era. Its novelty lies in synthesizing performance analysis with advanced network visualizations to define a dynamic research agenda, rigorously documenting the crucial shift where digital intelligence is no longer a supportive tool but the key enabler of sustainable and resilient supply chains.